Citrus limon rootstocks in Santa Catarina, Brazil - Koller, Osvino Leonardo; Soprano, Eliséo (Pesquisa Agropecuaria Brasileira, 1992)
Fifteen citrus cultivars were tested as rootstock for 'Siciliano' lemon, at the humid climate conditions of the State of Santa Catarina, where Phytophthora is causing serious damage. In order to obtain lower Phytophthora infection on lemon trees, the rootstocks must be not only Phytophthora resistant, but also have and induce low vigor to the scion, as sour orange and 'Cleopatra' mandarin. It is also recommended bud lemons at least 40 cm above the ground level, immediately below the canopy formation point, so that the major part of the trunk will be formed by a gummosis resistant rootstock.